TI-PAD BUDGET FOR ETS RELATED ISSUES. EXPERT WITNESSES USED IN 1994 (Tufts Archival Research Center, 2007)
Marginalia; Budget for the Tobacco Institute's environmental tobacco smoke budget. Includes mostly legal fees and a list of witnesses, dates they testified on behalf of the Institute and the amount they were paid.